2020
DOI: 10.1186/s12884-020-03013-8
|View full text |Cite
|
Sign up to set email alerts
|

The burden of adolescent motherhood and health consequences in Nepal

Abstract: Background: Annually, 18 million babies are born to mothers 18 years or less. Two thirds of these births take place in South Asia and Sub-Saharan Africa. Due to social and biological factors, adolescent mothers have a higher risk of adverse birth outcomes. We conducted this study to assess the incidence, risk factors, maternal and neonatal health consequences among adolescent mothers. Methods: We conducted an observational study in 12 hospitals of Nepal for a period of 12 months. Patient medical record and sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 21 publications
2
29
1
2
Order By: Relevance
“…13,14 In the study conducted in Nepal, finding has shown that nearly 2/3 rd of females were married before the age of 19 years in the year 2017/18. 15,16 Furthermore, this trend was mostly prevalent in families from lower economical groups. On the other hand, it has also been found that women having higher level of educational status have higher preference for CS.…”
Section: Introductionmentioning
confidence: 96%
“…13,14 In the study conducted in Nepal, finding has shown that nearly 2/3 rd of females were married before the age of 19 years in the year 2017/18. 15,16 Furthermore, this trend was mostly prevalent in families from lower economical groups. On the other hand, it has also been found that women having higher level of educational status have higher preference for CS.…”
Section: Introductionmentioning
confidence: 96%
“…Similarly, early pregnancies are also considered as a universal burden covering all countries irrespective of their economic status (4). It has been estimated that around sixteen million girls between the age of [15][16][17][18][19] years give birth each year globally and babies delivered from theses teen-age mothers occupies 11% of total birth worldwide. It is staggering to note that highest numbers (around 95,153) of such early pregnancies occurs in Eastern-Asia (5).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-parity, teen-age pregnancy, less or no antenatal visits being some of the basic key indicators of the vaginal delivery at home (13,14). In the study conducted in Nepal, nding has shown that nearly 2/3rd of females were married before the age of 19 years in the year 2017/18 (15,16). Furthermore, this trend was mostly prevalent in families from lower economical groups.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents are vulnerable to pregnancy and childbirth due to several adverse health and socioeconomic consequences both for mother and child 1,2 . Adolescent mothers had the risk of prolonged labor pain, preterm birth, and malnourished babies 3 . Pregnancy during adolescence is considered a sexual and reproductive health problem and a leading cause of maternal death especially for low‐ and middle‐income countries (LMICs) 4,5 .…”
Section: Introductionmentioning
confidence: 99%